Short-segment fixation and transpedicular bone grafting for the treatment of thoracolumbar spine fracture - Luo, Zhi-Wen; Liao, Wei-Jie; Sun, Bo-Lin; Wu, Jia-Bao; Zhang, Ning; Zhang, Yu; Huang, Shan-Hu; Liu, Zhi-Li; Zhang, Zhi-Hong; Liu, Jia-Ming (Frontiers in Surgery, 2023)
Purpose: Thoracolumbar fracture is one of the most common fractures of spine. And short-segment posterior fixation including the fractured vertebra (SSPFI) is usually used for the surgical treatment of it. However, the outcomes of SSPFI for different types of thoracolumbar fractures are not clear, and whether it is necessary to perform transpedicular bone grafting is still controversial. This study was conducted to determine the clinical efficacy of SSPFI for the treatment of different types of single-level thoracolumbar fracture, and make clear what kind of fractures need transpedicular bone grafting during the surgery. Methods: Patients with single-level thoracolumbar fracture undergoing SSPFI surgery between January 2013 and June 2020 were included in this study. The operative duration, intraoperative blood loss, anterior vertebral height ratio (AVHR) and anterior vertebral height compressive ratio (AVHC) of the fractured vertebra, local kyphotic Cobb angle (LKA), vertebral wedge angle (VWA) and correction loss during follow up period were recorded. Outcomes between unilateral and bilateral pedicle screw fixation for fractured vertebra, between SSPFI with and without transpedicular bone grafting (TBG), and among different compressive degrees of fractured vertebrae were compared, respectively. Results: A total of 161 patients were included in this study. All the patients were followed up, and the mean follow-upped duration was 25.2±3.1 months (6-52 months). At the final follow-up, the AVHR was greater, and the LKA and VWA were smaller in patients with bilateral fixation (6-screw fixation) than those with unilateral fixation (5-screw fixation) of AO type A3/A4 fractures (P<0.001). The correction loss of AVHR, LKA and VWA in fractured vertebra were significantly great when preoperative AVHC was > 50% (P<0.05). For patients with AVHC >50%, the correction loss in patients with TBG were less than those without TBG at the final follow-up (P<0.05). Conclusions: SSPFI using bilateral fixation was more effective than unilateral fixation in maintaining the fractured vertebral height for AO type A3/A4 fractures. For patients with AVHC > 50%, the loss of correction was more obvious and it can be decreased by transpedicular bone grafting.